PM Launches UMP Green Tech Project - UMP, PNC
Malaysia Prime Minister, Yang Amat Berhormat Dato’ Sri Mohd Najib Tun Abdul Razak, paid Universiti Malaysia Pahang’s (UMP) Pekan Campus an official visit on March 12, 2011, to launch the university’s green technology project, involving the development of the base oil extraction technology to recycle used lubricant oil.